PEMAKNAAN IDEOLOGIS PERJUANGAN RAKYAT PALESTINA DALAM CERITA PENDEK JABALUN-NÂR KARYA ALI AT-THANTAWY - Fadlil Manshur (LITERA, 2012)
This study aims to explain issues of Palestinian people’s struggle against the English occupation in Ali At-Thantawy’ short story Jabalun-Nâr. It employed the theories of genetic structuralism and ideology. The findings are as follows. First, Palestinian people’s responses to the fate of their nation occupied by English people are reflected in the behaviors of two main characters, Irfan and Mukhtar. Second, in social reality, Palestinian people face their nation’s internal challenges, namely the unstable and explosive political-military conditions in struggling against the English occupation on the Paletinian land. Third, the two main characters are effective subjects of thoughts capable of penetrating Palestinian people’s minds with the nationalism spirit to fight against the English occupation. Fourth, the meaning of Jabalun-Nâr is ‘volcano’, a symbol of Palestinian people’s strength successful in defeating English colonists.